Diferenciación de pautas de comportamiento del venado con ayuda de radiotransmisores con sensor de movimiento - Mandujano, Salvador; Pérez Arteaga, Alejandro; Gallina, Sonia; Sánchez Mantilla, Rosa Elena (Instituto de Ecología, A.C., 1996)
The objetive of this study was to know which behaviorai patterns of the white-tailed deer (OdocoHeus virginianus) we could reliably distinguished with motion-sensitive radio collars (model 400 Telonics). Behaviorai patterns and pulse rate (number of "beeps" per minute) were recorded simultaneously, using five penned deer during a total of 40 hours of observation in July 1994, at the laboratorio del Bosque la Primavera in Guadalajara, Jalisco. Twenty-one of the twenty-four different behaviors couldn't be identified reliably using this radiotransmisor model. Three types of behavior oan he differeritiated using this technique: if the number of "beeps" per minute vanes between 50 and 55, thore is a probability of 88% that the animal is lying down; a number of "beeps" between 56 and 69 the animals are searching for food (standing, waiking, and eating while waiking); and those animals with 70 to 87 "beeps" per minute spend more than 60% of their time eatmg almost exclusively in one spot, li was determinad that with a seven-minute reading of the number of "beeps," less errors were made in the classification of the behaviorai categories.s, radiotelemetry, white-tailed deer.